Ekonomi Islam sebagai Paradigma Etis dalam Transformasi Bisnis Modern Berkelanjutan: Kajian Perbandingan dengan Ekonomi Konvensional - M. Ferdiyan; Anisah Harahap (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes the comparison between Islamic economic principles and conventional economics in shaping a modern business paradigm that is ethical and sustainable. Through a qualitative approach based on literature review, this study identifies differences in value orientation, financial structure, and social implications of the two economic systems. The results show that Islamic economics, with its principles of maqashid sharia, distributive justice, and prohibition of usury, is capable of creating a more inclusive business model oriented towards social welfare. Data from the OJK, Bank Indonesia, and the Islamic Development Bank show an average growth of 9% per year in sharia assets and an increase in the MSME financing ratio to 71%. Meanwhile, the conventional economy is still dominated by short-term profit logic that often disregards ethical values and social balance. This study emphasizes that the integration of Islamic values into modern economic policy can be a strategic solution to realize a sustainable business system that is in line with the principles of justice and universal welfare.